METHOD OF DETERMINING THE TIME PARAMETER OF THE GAS GENERATOR HYDROGEN STORAGE AND SUPPLY SYSTEMS - Abramov, Y.; Kryvtsova, V.; Mikhailyuk, А. (Municipal economy of cities (Technical science), 2022)
The method of determining the hourly parameter of the main element of the system for saving and supplying water, the gas generator, has been developed. The method is based on the approximation of a partial frequency response for the phase-frequency characteristic of the gas generator of the water saving system in terms of frequency. This approximation is used to construct a mathematical dependence, which is used in determining the time parameter of the gas generator. In the quality of the cob data, when the hourly parameter of the gas generator is determined, the phase-frequency characteristic of the gas generator and the allowable values of the parameters of the characteristics and the parameters of the hourly parameter of the gas generator and the approximation of the first dynamic characteristic are recorded. To determine the frequency parameters, tolerance criteria for accuracy are used, with the help of such gains of analytical reliability of these frequency parameters in the form of variances. It is shown that the phase-frequency characteristic of the gas generator of the system for saving and supplying water is mainly carried out from the variation of the transitional function. For this purpose, an array of experimental data, obsessions, as a result of vimiryuvan in a discrete moment and time, is scored by the Kotelnikov-Nyquist-Shannon theorem. For the implementation of the method, a sequence of procedures was induced to ensure the determination of the hourly parameter of the gas generator. Verification of the method is marked by the way of the completion of the test task. It is shown that the change in the hourly parameter of the gas generator of the system for saving and supplying water does not exceed 1.0%.